2017
DOI: 10.1016/j.jchromb.2017.06.028
|View full text |Cite
|
Sign up to set email alerts
|

A review of high performance liquid chromatographic-mass spectrometric urinary methods for anticancer drug exposure of health care workers

Abstract: The medical treatment of cancer with antineoplastic drugs is routine, but careful biomonitoring for these powerful drugs in individual healthcare worker exposure is necessary to ensure that engineering controls and exposure intervention measures are effective. This review describes published high performance liquid chromatography/mass spectrometry (HPLC-MS) methods for the determination of anticancer drugs in human urine as non-invasive tools for monitoring of healthcare worker exposure to antineoplastic and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 55 publications
(95 reference statements)
0
16
0
Order By: Relevance
“…While the research on surface and biological monitoring for ADs has continued with enthusiasm, demonstrated by the number of recent publications reporting improved technology for wipe [23][24][25] and urine [26][27][28] sampling, only a limited number of the studies published consider both matrices [11,13,29].…”
Section: Introductionmentioning
confidence: 99%
“…While the research on surface and biological monitoring for ADs has continued with enthusiasm, demonstrated by the number of recent publications reporting improved technology for wipe [23][24][25] and urine [26][27][28] sampling, only a limited number of the studies published consider both matrices [11,13,29].…”
Section: Introductionmentioning
confidence: 99%
“…The literature includes many reports on the analysis of individual anticancer drugs, either in a pharmaceutical formulation, environmental samples or biological sample. [7][8][9] However, this is the first report on different analytical aspects and methodologies for the quantification of anticancer drugs covering almost all biological matrices. In this review, we have discussed the techniques of analysis of anticancer drugs published in the last 10 years and organized them based on different biological matrices.…”
Section: Introduction 719 2 Modern Analytical Techniques For Bioanalymentioning
confidence: 99%
“…The limit of detection (LOD) value in urine, for six of them, is from 0.0132–34 to 0.02 ng/L 35. For the others, the LOD value in urine is from 0.05 to 1 ng/L 36…”
Section: Introductionmentioning
confidence: 99%